Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1200/jco.20.00201
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Nivolumab for Patients With Resectable Merkel Cell Carcinoma in the CheckMate 358 Trial

Abstract: PURPOSE Merkel cell carcinoma (MCC) is a rare, aggressive skin cancer commonly driven by the Merkel cell polyomavirus (MCPyV). The programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1) immunosuppressive pathway is often upregulated in MCC, and advanced metastatic MCC frequently responds to PD-1 blockade. We report what we believe to be the first trial of anti–PD-1 in the neoadjuvant setting for resectable MCC. METHODS In the phase I/II CheckMate 358 study of virus-associated cancer types, patients with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
123
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(153 citation statements)
references
References 36 publications
1
123
0
6
Order By: Relevance
“…Pembrolizumab and nivolumab have shown similar efficacy in metastatic disease, and their approval in this setting is a certainty. Although there are no head-to-head trials comparing checkpoint inhibitors with CT, the results of this new immunotherapy-based approach compare favourably with historical data for CT in advanced MCC, especially in terms of safety features and durability of response 9–11…”
Section: Discussionmentioning
confidence: 89%
“…Pembrolizumab and nivolumab have shown similar efficacy in metastatic disease, and their approval in this setting is a certainty. Although there are no head-to-head trials comparing checkpoint inhibitors with CT, the results of this new immunotherapy-based approach compare favourably with historical data for CT in advanced MCC, especially in terms of safety features and durability of response 9–11…”
Section: Discussionmentioning
confidence: 89%
“…When used in a first-line setting, PD-1/PD-L1 inhibitors including avelumab, pembrolizumab, and nivolumab are even more promising as objective responses were observed in ∼50-70% of patients with a 2-year survival rate of about 70%. Due to these results, PD-1/PD-L1 inhibitors are considered the standard of care in advanced MCC and are currently being investigated in the adjuvant and neoadjuvant settings (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, an objective response rate over 50% was reported. Of note, responses were observed in both patients with virus-positive tumors and those with virus-negative tumors (9)(10)(11).…”
Section: Figure 1 | Continuedmentioning
confidence: 96%
See 1 more Smart Citation
“…Among 33 radiographically evaluable patients who underwent surgery, 18 (54.5%) had a tumor reduction ≤30%. During a median follow‐up of 20.3 months, median recurrence‐free survival (RFS) and OS were not reached 28 …”
Section: Checkpoint Inhibitors In Metastatic MCCmentioning
confidence: 99%